Microstructural and geomechanical study on biocemented sand for optimization of MICP process - Mujah, D.; Cheng, Liang; Shahin, M. (American Society of Civil Engineers (ASCE), 2019)
© 2019 American Society of Civil Engineers. Limited research has been reported on strength improvement of biocemented soils in relation to crystal patterns of microbially induced calcite (CaCO3) precipitation (MICP). In this study, sand samples were treated under the coeffect of different bacterial culture (BC) and cementation solution (CS) concentrations to evaluate the optimum BC and CS combination that yields the highest soil strength. It was found that for lower CS conditions (0.25 M), higher BC produced stronger samples, whereas for higher CS conditions (0.5 M or 1 M), lower BC was more dominant in improving the soil strength. This can be attributed to the effectively precipitated CaCO3 crystals, which were in rhombohedral shape and large size and were concentrated at the soil pore throat rather than deposited on the individual sand grain surface. This finding was confirmed with the scanning electron microscopy (SEM) analysis. The strength and permeability of the optimized biocemented samples were also compared with sand samples treated with ordinary portland cement (OPC). The optimized biocemented sand provided higher strength and permeability than those obtained from the samples treated with similar content of OPC at a curing period of 28 days.